Avoiding unintentionally correlated shocks in proxy vector autoregressive analysis - Martin Bruns; Helmut Lütkepohl; James McNeil (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
The shocks in structural vector autoregressive (VAR) analysis are typically assumed to be instantaneously uncorrelated. This condition may easily be violated in proxy VAR models if more than one shock is identified by a proxy variable. Correlated shocks may be obtained even if the proxies are uncorrelated and satisfy the usual relevance and exogeneity conditions individually. Examples from the recent proxy VAR literature are presented. It is shown that assuming uncorrelated proxies that satisfy the usual relevance and exogeneity conditions individually actually over-identifies the shocks of interest and a Generalized Method of Moments (GMM) algorithm is proposed that ensures orthogonal shocks and provides efficient estimators of the structural parameters. It generalizes an earlier GMM proposal that works only if at least K - 1 shocks are identified by proxies in a VAR with K variables.
Keywords: C32; C36; E52; 330; Structural vector autoregression; proxy VAR; external instruments; correlated shocks; Generalized Method of Moments